Pragmatics of Power: How Dedi Mulyadi Constructs Authority through Language - Mahmud, Fitriningsih Pratiwi; Talaohu, Ahmad Rifani; Maulud, Ismail (AL LUGHAWIYAAT: JOURNAL OF ENGLISH LANGUAGE TEACHING, 2025)
This study examines the pragmatic strategies through which Indonesian political figure Dedi Mulyadi constructs authority in his public communication. The significance of this research lies in highlighting how authority is enacted linguistically in Indonesian politics, where cultural values, humour, and symbolic expressions shape leadership discourse. The purpose of this article is to analyze how Dedi Mulyadi uses speech acts, politeness strategies, conversational implicatures, and code-mixing to project authority while sustaining solidarity with audiences. The analysis applies Speech Act Theory (Austin, 1975; Searle, 1969), Politeness Theory (Brown & Levinson, 1987), and Grice’s (1975) theory of implicature. Methodologically, this research adopts a qualitative design using pragmatic discourse analysis. Data were collected purposively from Dedi Mulyadi’s speeches, interviews, and informal talk shows retrieved from YouTube channels, news portals, and other online platforms in 2025. Transcriptions were coded to identify illocutionary acts, politeness strategies, and implicatures within cultural contexts. Findings reveal that Dedi Mulyadi combines assertiveness with inclusivity, frequently using directives and assertives framed through humour, cultural metaphors, and rural imagery. His code-mixing in Sundanese and Bahasa Indonesia strengthens local identification, while implicatures allow him to convey moral imperatives indirectly. Overall, these pragmatic strategies enable him to project power while simultaneously constructing an approachable, culturally grounded leadership persona.